2016
DOI: 10.1016/j.pnucene.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Startup instability in natural circulation driven nuclear reactors

Abstract: Natural circulation driven nuclear reactors are prone to flow instability during the startup transients. This paper intends to provide the state-of-the-art reviews on the theoretical analysis and experimental studies on flow instability in three types of natural circulation driven reactors, ranging from conventional nuclear reactors to small modular reactors. Brief overviews of three categories of startup flow instability, i.e., density wave oscillations, flashing instability, and Geysering instability, are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The basic method used in this research to study the flashing instability is called linear frequency domain stability analysis, which can be used to obtain stability boundaries for a flow system. This method is a conventional way to analyze other flow instabilities such as the density wave oscillations (DWO) [1] and Ledinegg instability (flow excursion) etc. The frequency domain analysis in this research was based on the drift-flux model and its constitutive equations [18] for a two-phase flow system.…”
Section: Frequency Domain Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The basic method used in this research to study the flashing instability is called linear frequency domain stability analysis, which can be used to obtain stability boundaries for a flow system. This method is a conventional way to analyze other flow instabilities such as the density wave oscillations (DWO) [1] and Ledinegg instability (flow excursion) etc. The frequency domain analysis in this research was based on the drift-flux model and its constitutive equations [18] for a two-phase flow system.…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…The flashing induced stability problem, simplified as flashing instability, in two-phase flow system is of great importance to the safe operation of naturally driven nuclear reactors and passively safe engineering safety system in nuclear industry. The designs of naturally driven nuclear reactors, ranging from conventional nuclear reactors to small modular reactors [1], feature a relative long chimney section above the reactor core to increase the driving force of natural circulation. In addition, the design of the reactor cavity cooling system for the generation IV reactors characterizes a long riser above the cooling panel [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the opposite if P in is large enough, boiling occurs in the heated section and nonlinear phenomena happen. Past works [2][3][4][5][6][7][8][9][10][11][12] have shown that natural circulation exchanger are stable at low P in and high subcooling T sat − T in (with T sat the saturation temperature), and exhibit strong flow reversals at high P in and low T sat − T in . These works included theoretical, experimental and numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…More recently the occurrence of the natural circulation in nuclear research reactors has been described in the literature by studies focusing mainly: the prevention of a severe accident [8], the effect of an unprotected reactivity insertion on the dynamic response of Materials Testing Reactor -MTR research reactors under natural circulation regime [9], the investigation of flow reversal from downward forced to upward natural circulation [10], the stability of the natural circulation and its suppression due to the presence of oscillations [11], [12].…”
Section: Introductionmentioning
confidence: 99%